Antioxidant Potential, Total Phenolic and Flavonoids Content of Aerial Parts of Ethanolic Extract of Cordia Obliqua - S. Sivakrishnan (Journal of Global Pharma Technology, 2019)
Objective: The aim of this work was to estimate the total phenolic and flavonoids content, and to evaluate in-vitro antioxidant activity of ethanolic extract of Cordia obliqua.Methods: The ethanolic extract of Cordia obliqua was examined by Iron chelating activity, Total antioxidant activity, Total phenol and flavonoids with reference standard EDTA (Ethylenediaminetetraacetic acid), Ascorbate and catechol respectively through in vitro models.Results: The antioxidant activities of the extract were positively associated with the total phenolic and flavonoid contents of the ethanolic extract of cordia obliqua.Conclusion: Ethanolic extract of Cordia obliqua. showed strong scavenging activity. These in vitro assays indicate that this plant extract is a better source of natural antioxidants. The presence of antioxidants such as phenolics, flavonoids, tannins and proanthocyanidins in plants may provide protection against a number of diseases including cancer, neurodegeneration and inflammation.